ANALISIS PELAKSANAAN BIMBINGAN KARIER OLEH GURU BIMBINGAN KONSELING PADA PESERTA DIDIK KELAS XI SMA - Ruhama, Ummi; Purwanti, Purwanti; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCareer guidance is a guidance activity that is specifically aimed at helping learners to make career choices and decisions appropriately. This study aims to analyze the implementation of career counseling in class XI high school students. The method used is descriptive method with Survey Studies research form. The data collection techniques used are direct communication techniques and indirect communication. Data collection tools are interview guides and questionnaires. Data analysis techniques using percentage analysis techniques and qualitative analysis.The population in this study amounted to 232 learners and one of the Counseling Guidance Teachers. The number of learners used as many as 25% or 58 students are selected at random. Based on the results of data analysis, it can be said that the implementation of career guidance by Counseling Guidance Teachers in grade XI SMA students reached the actual score of 548 and the ideal maximum score of 580 means reaching 94% are in the category of